COMPARATIVE ANALYSIS OF BIOLOGICALLY ACTIVE COMPLEXES OBTAINED BY THE SCF COF METHOD - PLANT EXTRACTION OF PLANTS OF DAUCUS CAROTA, SOLANUM LYCOPERSICUM, CRATAEGUS TURKESTANICA A. POJARK SPECIES - Ikhsanov Yerbol Saginovich; Burashev Yerlan Mahatovich; Seitimova Gulnaz Absattarovna; Litvinenko Yuliya Alekseevna (Academic Scientific Journal of Chemistry, 2019)
The article presents the results of a study of the qualitative and quantitative extracts obtained by the method of supercritical fluid extraction by carbon dioxide from the fruits of the plant Daucus carota, Solanum lycopersicum, Crataegus turkestanica A. Pojark. Extraction on a Thar SFE-1000 CO2-extraction unit under the following conditions: temperature range in the reactor is 40-80 ° C, CO2 pressure is 180-200 bar, with a gas flow of 100 ml / min, ethyl alcohol was used as a cosolvent. The obtained extract was investigated by gas chromatography on a gas chromatograph with an Agilent Technologies 7890N / 5973N GC / MS mass-selective detector. The studied extracts identified in Daucus carota: carotenoids, limonene (0.2%), o-cymol (0.29%), cariofillen (0.3%), phytol acetate (4.25%), eicosane (1.2 %), falkarinol (4.5%), squalene (0.8%), vitamin E (0.6%), campesterol (0.8%), stigmasterol (2.34%), gamma sitosterol (2.49 %). Crataegus turkestanica A. Pojark: Limonene (0.42%), o-cymol (0.28), phytol acetate (1.45%), eicosane (3.65%), falkarinol (0.255%), squalene (2, 0%), vitamin E (0.57%), campesterol (0.78%), alpha-tocopherol (1.83%), gamma-sitosterol (4.83%). Solanum lycopersicum: Carotenoids, fatty acid esters (oleic, linolenic, hexadecanoic, octadecadienoic), eicosane (2.65%), lupeol (2.33%), phytol acetate (1.61%), alpha-amyrin (7.46 %), vitamin E (1.08%), tetracosane (3.81%) For a more complete study of the chemical composition of supercritical extracts of the extract, gas chromatography with a mass selective (GC-MS) detector was used. Work on the study of extracts obtained under other conditions of extraction is currently ongoing.